Learning, understanding and recognizing the importance of formal and semantic congruence between music and sports routines - Loo, Fung Chiat; Loo, Fung Ying (International Academy of Technology, Education and Development, 2024)
While music is common in many sports routines and dances, several similarities exist between music and movement. Music is often used simply as background music or sound, which defeats its actual purpose and ignores the effects of combining of both subjects. Both formal and semantic congruence are available in the fields of music and movement and have been studied extensively. The current study elucidates the scientific and philosophical evidence demonstrating the similarities between music and movement. This study also emphasizes the importance of learning and understanding similarities in the congruence between music and sports routines to maximize the effect of the combination of both subjects. The research methods included a comparative analysis of literature from the fields of movement and music. Through experiments and surveys, this study also proved that increased congruence between subjects enhanced the perceived qualities in many aspects. The result also showed that respondents with music training backgrounds were more capable of recognizing and understanding perceived congruence. The purpose of this study was to encourage the recognition and learning of music to increase understanding of its use in other domains, rather than using music merely as a background sound in a subjective preference. This indicates that musical knowledge and education are essential in the fields of various multimedia and film music.